Peran Balai Pemasyarakatan Dalam Upaya Diversi Terhadap Tindak Pidana Pencurian Yang Dilakukan Oleh Anak - Syabarani*, Annisa; Sukmareni, Sukmareni; Fitri Z, Yenny (Universitas Syiah Kuala, 2023)
This study aims to determine the role of Correctional Centers in efforts to diversion of criminal acts of obscenity with children as the perpetrators of the case in Bukittinggi and to determine the obstacles to implementing diversion of children who are in conflict with the law in Class II Correctional Centers Bukittinggi. The type of research used is Empirical Legal research, using primary and secondary data. Then analyze the data by describing the data that has been collected as it is without intending to make general conclusions or generalizations using descriptive techniques. The results of the study are the role of correctional centers in diversion efforts. And the crime of theft of Article 363 paragraph 1 5e of the Criminal Code in conjunction with Law Number 11 of 2012 Concerning the Juvenile Justice System, which was committed by a child at the Bukittinggi class II Correctional Center, was successfully carried out by diversion with a decision to return stolen goods and compensation with money Court diversion And the obstacles to the implementation of diversion against children in conflict with the law are obstacles originating from the victims' families themselves, regulations between the police and the Correctional Center, and the distance traveled between the Class II Correctional Center of Bukittinggi. The efforts made by the correctional center in carrying out diversion of children in conflict with the law are by holding outreach from the Bukittinggi Class II Correctional Center to the community as a whole and providing counseling to the community so that they understand and the importance of the role of the correctional center in diversion of cases committed by children.